2023
DOI: 10.1021/acsbiomaterials.2c00723
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Loading-Induced Cartilage Self-Heating in Vitro Promotes Matrix Formation in Chondrocyte-Laden Constructs with Different Mechanical Properties

Abstract: Articular cartilage presents a mechanically sensitive tissue. Chondrocytes, the sole cell type residing in the tissue, perceive and react to physical cues as signals that significantly modulate their behavior. Hyaline cartilage is a connective tissue with high dissipative capabilities, able to increase its temperature during daily activities, thus providing a dynamic thermal milieu for the residing chondrocytes. This condition, self-heating, which is still chiefly ignored among the scientific community, adds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
(95 reference statements)
2
16
0
Order By: Relevance
“…While it could be argued that our channel analysis has only been performed in free-swelling constructs and not in stimulated hydrogels, we have previously shown that thermomechanical loading increases the expression of these channels at protein levels as well. 12,26 Hence, we contend the validity of our hypothesis, suggesting that the observed effects likely arise from the interplay between various stimuli and the multifaceted responses of chondrocytes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…While it could be argued that our channel analysis has only been performed in free-swelling constructs and not in stimulated hydrogels, we have previously shown that thermomechanical loading increases the expression of these channels at protein levels as well. 12,26 Hence, we contend the validity of our hypothesis, suggesting that the observed effects likely arise from the interplay between various stimuli and the multifaceted responses of chondrocytes.…”
Section: Discussionmentioning
confidence: 58%
“…Our previous studies have extensively elucidated the significance and relevance in replicating cartilage self-heating in vitro and demonstrated thoroughly how loading-induced evolved temperature can be harnessed in vitro to accelerate tissue maturation through expression of major structural proteins. 26 Building upon our prior findings where load, heat and hypoxia interactions were studied, herein we aimed to introduce the inherent dynamic nature of the culture environment as an additional parameter in this multifaceted equation. The relevance of including PEG/alpha cyclodextrin-based polyrotaxanes into the robust covalent network stems from their capacity to partially replicate the dynamic interactions found in natural cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In our investigation, the hydrogel formulations were also subjected to bioreactor culture conditions that incorporated thermomechanical signals under a low oxygen tension. Our previous studies have extensively elucidated the significance and relevance in replicating cartilage self-heating in vitro and demonstrated thoroughly how loading-induced evolved temperature can be harnessed in vitro to accelerate tissue maturation through expression of major structural proteins. ,, Building upon our prior findings where load, heat, and hypoxia interactions were studied, herein we aimed to introduce the inherent noncovalent nature of the culture environment as an additional parameter in this multifaceted equation. The relevance of including PEG/alpha cyclodextrin-based polyrotaxanes into the robust covalent network stems from their capacity to partially replicate the dynamic interactions found in natural cartilage. , Through the incorporation of supramolecular polyrataxanes, we aim to mimic the innate noncovalent interactions inherent in cartilage tissue, playing a pivotal role in its mechanical composure and potential signals they transfer to chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We identified three ion channels, namely, TREK1, TRPV4, and PIEZO1, whose expression was significantly upregulated in the presence of host–guest reversible polyrotaxanes. While it could be argued that our channel analysis has only been performed in free-swelling constructs and not in stimulated hydrogels, we have previously shown that thermomechanical loading increases the expression of these channels at protein levels as well. , Hence, we contend with the validity of our hypothesis, suggesting that the observed effects likely arise from the interplay between various stimuli and the multifaceted responses of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the manufacturing phase and following transport/storage, the constructs were evaluated via macroscopic assessment, cell viability assessment, total GAG quantification, and histology for three different transport media (Table 4). [69][70][71]. In order to meet increasing clinical needs, important translational efforts are being allocated toward the optimization of existing ACI protocols or the creation of novel approaches [11,12,[72][73][74][75][76].…”
Section: Allogeneic Finished Products Possess An Appropriate Pharmace...mentioning
confidence: 99%